Warriors : A Shadow in RiverClan - Book 1 - Jolley, Dan; Hunter, Erin; Barry, James L., 1979- (New York, NY : Harper Alley, an imprint of HarperCollinsPublishers, 2020)
When RiverClan fell under the rule of the vicious Tigerstar, Feathertail barely escaped with her life. Now RiverClan is trying to rebuild in unity and peace--even if Feathertail isnt ready to forgive her Clanmates. But when RiverClan takes in a rogue cat named Sasha and her two kits, Feathertail must find a way to escape the shadows of the past if she is to be a part of her Clans future.
Keywords: Cats -- Juvenile fiction; Survival -- Juvenile fiction; Leadership -- Juvenile fiction; Comics (Graphic works); Graphic novels; Graphic novel adaptations